The Relationship Between Quality of Work Life and Job Satisfaction Among Nurses in a Teaching Hospital in 2020 - Maryam Dargahpour; Parisa Jalali; Mohsen Mohammadi (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Job satisfaction and the quality of work life are measured as indicators of organizational development in many studies.Work's nurses affected from this two variables .This research aims to study the relationship between quality of work life and job satisfaction among nurses. Methods: This was a descriptive analytic study. Research population included 538 nurses in Golestan hospital in Ahvaz in 2020.  111 nurses were selected through simple random sampling. Data collection instruments were Walton quality of work life and Whiskey and Chrome job satisfaction questionnaires. The reliability and validity were measured. Data were analyzed through descriptive statistics, Pearson correlation analysis, independent t-test and ANOVA in SPSS20. Results: In this study, 32.40 % of the participants were male and 67.60 % were female. Quality of work life and job satisfaction showed a significant and moderate correlation (r = 0.36, P-value < 0.001).  Results indicated a significant correlation between job satisfaction and components of quality of work life (P-value< 0.05), except for the general atmosphere of working life (P-value> 0.05). There was no significant correlation between the study's variables and demographic characteristics. Conclusion: There is a significant relation between the quality of work life and job satisfaction. Job satisfaction among nurses in Ahvaz hospitals can be increased by implementing programs to improve the quality of work life.